Determination of the Groundwater Recharge Coefficient of the Upper Cisadane River - Cisadane Sub-Watershed - Karmadi, Muhammad Agus (Universitas Pakuan, 2024)
Recharge groundwater naturally manifested by curved shrinkage (recession curve) elementary streams (base flow) is a very important component of the flow stream produced by the inflow through the process of rainfall infiltration into percolation and finally donated to soil water deposits.This research aims to know the quantity of groundwater Coefficient Recharge tentative Natural Cisadane River Watershed with an area of 842.69 Km², where the magnitude of the suffixes can be used as the basis for the determination of soil water uptake in the region allow question-based environment that is sustainable, so that sustainable utilization/groundwater remain sustainable.In addition the value of the coefficient of the term can also be used to indirectly set the magnitude of the numerical groundwater in surrounding watershed in the process of regionalization.The most common watershed characteristics affecting large affixes which include variable rainfall, geology, soil infiltration rates, factor flow base, and land cover.The study was carried out to obtain the estimated average value of affix using Recessive Curves (curvilinear depreciation/recession curve) of the daily discharge data for the period 1980 – 2015 acquired from Water Resources R D Center in Bandung. The average rainfall value is sought by the Isohyet method and then the value of the additive coefficient (Recharge Coefficien) can be determined, by dividing recharge value and rainfall avarage of the watershed area. The Value of the Recharge Coefficient (RC) obtained based on a calculation of 0.14 %. While based on the calculation of the benefits that occur in rock formations get the value of the Recharge Coefficient (RC) of: 742.11 x 106 m3/year. The amount of groundwater that can be released or flowed during the dry/dry season is: 172.70 x 106 m3/year, or about 98.27 %. The decline in the contribution of the suffixes in the Cisadane River Watershed can impact on the depletion of water sources during the dry season.Therefore, the need to management of water resources and integrated watershed conservation efforts and sustainable as a solution decrease the suffixes, so that quality, quantity, and continuity of water resources on a watershed Cisadane can awake.